2009
DOI: 10.1007/s10661-009-1160-x
|View full text |Cite
|
Sign up to set email alerts
|

Sequential fractionation of phosphorus in sediments of El-Fayum lakes—Egypt

Abstract: The amounts and forms of potentially mobile phosphorus (P) in surface sediments of Qarun and Wadi El-Rayan lakes were evaluated during winter and summer using a sequential chemical extraction. Five sedimentary P fractions were separately quantified: loosely sorbed P (NH(4)Cl-P), iron-associated P (BD-P), calcium- bound P (HCl-P), metal oxide bound P (NaOH-P), and residual P (organic and refractory P). The results indicated that the fractional composition of the examined lakes was different while the total P co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Marine cymothoids are almost limited occupant of shallow water, little of them being known from long depths [11] . The depth of the collected Cymothoidae from the shallower (eastern basin) Location of Qarun Lake was 7m [17] that was appoximately similar to the environments of (Cymothoidae sp. Cy150091, (BAX37137)).…”
Section: Phylogeny Analysis and Interpretationmentioning
confidence: 77%
See 1 more Smart Citation
“…Marine cymothoids are almost limited occupant of shallow water, little of them being known from long depths [11] . The depth of the collected Cymothoidae from the shallower (eastern basin) Location of Qarun Lake was 7m [17] that was appoximately similar to the environments of (Cymothoidae sp. Cy150091, (BAX37137)).…”
Section: Phylogeny Analysis and Interpretationmentioning
confidence: 77%
“…All the previous annotations were used to annotate the accession number (LC138010.1) and produced the protein accession number (BAU78233.1). The depth of the shallower (eastern basin) Location of Qarun Lake, Fayoum, Egypt has a depth from 5m to 8.4m [17]. The main problem came from the Transferring the fingers of Mugil cephalus from Suez Gulf which infested by the Cymothoidae species.…”
Section: Phylogeny Analysis and Interpretationmentioning
confidence: 99%
“…The biogeochemical reactions of Fe and S also affect both availability of sedimentary P to aquatic organisms and mobility of P within the sediments (Rozan et al, 2002). Previous studies have shown that the extent of P release is thought to be controlled either by the redox conditions at the sediment-water interface and/or by the formation of authigenic P minerals in supersaturated pore waters (Abdel-Satar and Sayed, 2010;Ruttenberg and Berner, 1993;Rozan et al, 2002). It is widely accepted that reductive dissolution of iron oxides is a major mechanism responsible for the release of P (Ruttenberg and Berner, 1993;Rozan et al, 2002).…”
Section: Introductionmentioning
confidence: 99%